Transformasi Al-Washliyah: Dari Gerakan Kultural ke Politik Elektoral - RIZA, FAISAL (Politeia: Jurnal Ilmu Politik, 2013)
This article provides a consistent description of the al-Washliyah as a third largest Islamic organization in Indonesia, and the largest in North Sumatra, related to their participation in the contestation in local elections (elections). Specifically, this article describes the transformation of Al-Washliyah from the cultural movement to electoral politics. This article argues that there are two factors that underlie why the polarization of attitudes about participation in the organizations members as candidates in the election: (1) The structure of the organization itself, and (2) an open political atmosphere. A fortune that organizations like al-Islam Washliyah active as a civic organization, has the advantage of the network through the womens wing organizations, students, youth, welfare agencies, educationand other forms of public service that provides the opportunity and the chance to follow in pilkada. However, the transformation of the organizations involvement in electoral politics explains the tendency delivers attention to strategies of non-participatory could be beneficial for those with the potential to change the social order in non-electoral method.Keywords: Islamic organization, cultural movement, electoral politics.